Institutional Censorship in Relation to Catholic Press during the Decline of People’s Republic of Poland (1989–1990) - Kamińska-Chełminiak, Kamila (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The goal of the article is to present the scope of interventions by the Regional Offices for the Control of Publications and Performances in the Catholic press during the decline of the People’s Republic of Poland (PRL) and the first months of the Republic of Poland, i.e. between January 1989 and April 1990. Initial censorship was a period which preceded the Round Table talks while final censorship ended with the abolition of censorship, i.e. the passing of the act (11 April 1990) on the liquidation of the institutions for the control of publications and performances. The source material for the article were the files of the Main Office of Control of Press, Publications and Shows stored in the Archives of New Records.